2022
DOI: 10.3126/bjhs.v7i2.49304
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Post Exposure Prophylaxis of HIV among Nurses of a Private Hospital

Abstract: Introduction: There are many effective prevention interventions available for those experiencing occupational exposure, and post exposure prophylaxis (PEP) is one of them. Different studies worldwide have shown low utilization of PEP for HIV due to lack of adequate knowledge. Objective: The purpose of this study was to assess the knowledge on PEP of HIV among nurses. Methodology: Descriptive cross-sectional research design was used and all the 130 nurses working in a private hospital of Biratnagar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…7 However, studies have shown that nurses in Nepal and other countries may have insufficient knowledge about PEP for HIV. 8 To address this knowledge gap, it is important to conduct a study to assess nurses' knowledge and understanding of PEP for HIV in Nepal. This study can help identify areas where nurses may need further education and training, as well as inform policies and guidelines for HIV prevention and control in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, studies have shown that nurses in Nepal and other countries may have insufficient knowledge about PEP for HIV. 8 To address this knowledge gap, it is important to conduct a study to assess nurses' knowledge and understanding of PEP for HIV in Nepal. This study can help identify areas where nurses may need further education and training, as well as inform policies and guidelines for HIV prevention and control in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%